1993
DOI: 10.1159/000462376
|View full text |Cite
|
Sign up to set email alerts
|

Blood Transfusion and Immunomodulation : A Possible Mechanism

Abstract: To induce an immunogenic response in vivo, an antigen-presenting (stimulator) cell must present both antigen-specific (class II MHC) and an accessory signal to the CD4 T cell. Failure to express the accessory signal has been shown in vitro to induce a state of specific unresponsiveness (anergy) in the T cell. We have shown that although stimulator cells in blood continue to express class II MHC molecules during refrigerated storage, their ability to present the accessory signal diminishes, reaching zero in all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Therefore, it would be logical to implement measures to prevent these immunomodulatory effects of allogeneic blood transfusion. Because most evidence from studies in experimental animals implicates allogeneic WBCs in the production of the deleterious TRIM effects, 30,[37][38][39][40][41][42][43] and because universal WBC reduction of all transfused cellular blood components has been implemented in some western European countries and in Canada, 50,51 policy makers in the United States and elsewhere are currently considering the question of implementing universal WBC reduction for the purpose of preventing the various possible deleterious TRIM effects.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, it would be logical to implement measures to prevent these immunomodulatory effects of allogeneic blood transfusion. Because most evidence from studies in experimental animals implicates allogeneic WBCs in the production of the deleterious TRIM effects, 30,[37][38][39][40][41][42][43] and because universal WBC reduction of all transfused cellular blood components has been implemented in some western European countries and in Canada, 50,51 policy makers in the United States and elsewhere are currently considering the question of implementing universal WBC reduction for the purpose of preventing the various possible deleterious TRIM effects.…”
Section: Discussionmentioning
confidence: 99%
“…11,26,27 The mechanism(s) of the TRIM effect(s) also remains elusive, and it is possible that a large number of biologic mechanisms may underlie the effect(s). [28][29][30][31] The infusion of foreign antigen in either a soluble [31][32][33][34][35][36] or cell-associated [37][38][39][40][41][42][43] form has been shown to induce immune suppression, anergy, and clonal deletion in studies in experimental animals. However, most studies evaluating proposed mechanisms have been done in rodents, and these findings may not be applicable to the human immune system.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Mincheff et al (24) have shown that blood stored for 13 or more days loses its immunogenicity because its ability to present the accessory signal diminishes, with a Creatinine (mg/dl)(-¢-) consequent induction of some degree of immunosuppression.…”
Section: Discussionmentioning
confidence: 99%